Influence of Autoclaved Placenta Extracts on Phase Behavior of Cell Suspensions Below 0°C - Zinchenko, Aleksandra V.; Bobrova, Elena N.; Schetinsky, Miroslav I.; Govorova, Yulianna S. (Problems of Cryobiology and Cryomedicine, 2013)
Phase transitions in human placental extracts during cooling at -196°C and the effect of fresh and autoclaved extracts on phase transitions in cell suspensions were studied. It has been found that after cooling with the rate of 3.3(3)deg/s in cell suspensions or suspending media the process of crystallization termination developed at the stage of heating with the rate of 8.3(3)x10-3 deg/s. After dilution of the suspension of Candida albicans and SPEV cells with autoclaved extract this process was not observed. It was found that the crystallization of eutectic mixtures was developed in frozen placental extracts unlike the mixture of extracts with erythrocytes and C. albicans cells. Probl Cryobiol Cryomed 2013; 23(1):40-48.